Labial gland biopsy: shared care, medicolegal and surgical considerations. (3rd February 2019) - French, K.; Fleming, C.; Bell, C.; Staines, K.
Abstract: Aim: To give the surgeon an overview of Primary Sjögren's syndrome, its pathophysiology, diagnosis and management thus giving insight into why labial gland biopsies are required. The authors also aim to make the operating surgeon aware of their role, responsibility and medicolegal factors to be considered prior to undertaking a labial gland biopsy (LgBx). Materials and methods: A literature search of PubMed (MEDLINE), Cochrane and EMBASE electronic databases using the search terms 'Primary Sjӧgren's Syndrome', 'Diagnostic Criteria for Sjӧgren's Syndrome', 'Labial Gland Biopsy', 'Labial Gland Biopsy Complications', 'Diagnostic Imaging for Sjӧgren's Syndrome' and 'Medicolegal Responsibility of Surgeons'. Title and then abstract were reviewed to determine relevance. Widely used guidelines were identified, indications for biopsy and the risks posed by surgery considered. Medicolegal advice was formally sought via a medical/dental defence union. Results: The authors considered the available evidence and medicolegal advice and applied this knowledge to the clinical setting. A preoperative checklist for consideration prior to LgBx was developed. Conclusions: Labial gland biopsy is an invasive procedure with potential to cause post‐operative complications. The operator assumes ultimate responsibility for the procedure. Every surgeon aims to ensure safe surgical practice, in the best interest of the patient. Here, we consolidate recent evidence and propose a checklist to facilitate the process for oral surgeons.